Low molecular weight chitosan nanoparticulate system at low N:P ratio for nontoxic polynucleotide delivery - Alameh M (Dove Medical Press, 2012)
Mohamad Alameh, Diogo DeJesus, Myriam Jean, Vincent Darras, Marc Thibault, Marc Lavertu, Michael D Buschmann, Abderrazzak MerzoukiInstitute of Biomedical Engineering, Department of Chemical Engineering, École Polytechnique, Montréal, CanadaAbstract: Chitosan, a natural polymer, is a promising system for the therapeutic delivery of both plasmid DNA and synthetic small interfering RNA. Reports attempting to identify the optimal parameters of chitosan for synthetic small interfering RNA delivery were inconclusive with high molecular weight at high amine-to-phosphate (N:P) ratios apparently required for efficient transfection. Here we show, for the first time, that low molecular weight chitosan (LMW-CS) formulations at low N:P ratios are suitable for the in vitro delivery of small interfering RNA. LMW-CS nanoparticles at low N:P ratios were positively charged (ζ-potential ~20 mV) with an average size below 100 nm as demonstrated by dynamic light scattering and environmental scanning electron microscopy, respectively. Nanoparticles were spherical, a shape promoting decreased cytotoxicity and enhanced cellular uptake. Nanoparticle stability was effective for at least 20 hours at N:P ratios above two in a slightly acidic pH of 6.5. At a higher basic pH of 8, these nanoparticles were unravelled due to chitosan neutralization, exposing their polynucleotide cargo. Cellular uptake ranged from 50% to 95% in six different cell lines as measured by cytometry. Increasing chitosan molecular weight improved nanoparticle stability as well as the ability of nanoparticles to protect the oligonucleotide cargo from nucleases at supraphysiological concentrations. The highest knockdown efficiency was obtained with the specific formulation 92-10-5 that combines sufficient nuclease protection with effective intracellular release. This system attained >70% knockdown of the messenger RNA, similar to commercially available lipoplexes, without apparent cytotoxicity. Contrary to previous reports, our data demonstrate that LMW-CS at low N:P ratios are efficient and nontoxic polynucleotide delivery systems capable of transfecting a plethora of cell lines.Keywords: siRNA, nonviral delivery system, chitosan, gene silencing, RecQL1, ApoB